Policy Mobilities and Interdisciplinary Engagement. (13th September 2015) - Cook, Ian R.
Abstract: This essay explores the nature and potential of interdisciplinarity in the expanding body of research on the circulation of policies between places. It focuses on the policy mobilities literature, highlighting its geographical underpinnings as well as its links to, and divergences from, literature beyond geography, in particular the political science‐led work on policy transfer. Acknowledging the potential downfalls of interdisciplinarity, it calls for increased conversations and co‐working between geographers, political scientists and other social scientists to explore the topic further.